REDESAIN TERMINAL TIPE B KM. 6 KOTA BANJARMASIN DENGAN MENGOPTIMALKAN SIRKULASI - Putra, Adam Syahdama Mahendra; Febrita, Yuswinda (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
The background for the redesign of Terminal Type B km.6 in the city of Banjarmasin is thedevelopment plan and the current condition of the terminal. The current condition of the terminal hasproblems with facilities and circulation, where facilities at the terminal are difficult to identify, and arenot functioning properly. Circulation at the terminal often experiences crossing, this is due to unclearvehicle paths and leakage of human circulation in buildings. The purpose of redesign is to obtain anew design of the terminal, which meets the criteria, facilities and circulation with minimal crossings.The method used in this redesign is the behavioral architectural approach, which addresses theinteraction between humans and public spaces. The concept raised is interaction, where this conceptpays attention to spatial planning and circulation. The elaboration of the concept uses thesuperimpose method, which creates layers related to the concept on the layering which will becombined to create a new design. The result of this redesign is a terminal design that meets thecriteria as a type B terminal, and has regular circulation without crossing.